Modeling of an Adaptive Hydraulic Drive System for the Cutting Mechanism of a Stem Feed Loader - Kuzmenko, Volodymyr; Veselovska, Natalia; Rutkevych, Volodymyr; Shargorodskiy, Serghiy; Kholodiuk, Oleksandr (Z͡H︡urnal inz͡h︡enernykh nauk, 2025)
The article considers the problem of increasing the efficiency and cost-effectiveness of the mechanization means of block-portion separation of stem feed, which implements the principle of adapting the operation of the actuator hydraulic motors to the conditions of their load. The object of the study is the cutting mechanism of the stem feed loader, used in the technological processes of harvesting and issuing stem feed from trench storage in a block-portion mode. During the technical analysis, factors were identified that limit the efficiency of its use. In particular, the design of the standard hydraulic drive does not allow for full consideration of the unevenness of the load during the process of cutting and feeding the forage mass, which leads to increased energy consumption, instability, shutdown of mechanisms, and increased wear of moving parts. The density and moisture content of stem feed are non-uniform in volume, so that the cutting force can vary fairly. If this factor is not considered, the system will consume more energy. To solve this problem, a mathematical model of an adaptive hydraulic system was developed. The leading technical solution was the introduction of a mechanism for automatic regulation of the flow rate of the working fluid in real time according to the flow load on the drive, which allows the optimal operating mode of the system to be achieved. During the study, mathematical modeling and simulations were carried out. As a result, the power of the cutting mechanism drive was reduced to 5–6 kW. Compared with traditional approaches, the proposed adaptive system demonstrates better sensitivity to changes in the resistance of the environment and a quicker response to dynamic oscillations in the hydromechanical circuit.